Representation of the Past in Bernhard Schlink's Fiction - Dmitry A. Chugunov (Studia Litterarum, 2020)
The article aims to determine the place of Bernhard Schlink in the modern German literature. Despite the worldwide success of his novel The Reader, many of the writer’s subsequent writings were heavily criticized. The main objects of negative reviews were stylistic features of the narrative and insufficient depth of the characters’ psychology. However, perception of the writer as the author of ideological novels allows us to understand the real significance of his artistic experiments. Schlink takes a position of the intellectual writer who carefully analyzes trivial judgments about the past and the present. In his work, he touches upon different key points of the modern German concept sphere. The field of fiction, to which Schlink covertly appeals in his thoughts, provides his fiction with the presence of reference points shared by most readers. In this regard, relying on recognizable stories and images, intellectual communication with an educated reader capable of recognizing widely discussed and important topics that Schlink picks up — all this allows the writer to systematize many separate judgments about history and society.